Retracted article: Providing a decreasing connection probability model for urban street network - Ziari, Hasan; Behbahani, Hamid; Khabiri, Mohammed M. (Transport, 2006)
View retraction statement: We apologise for the presented paper considered as a typical example of PLAGIARISM. The earlier published initial original references:• B. Jiang, C. Claramunt. 2004. A structural approach to the model generalization of an urban street network, GeoInformatica 8 (2): 157-171.• B. Jiang, C. Claramunt. 2002. A structural approach to model generalisation of an urban street network, in 5th AGILE Conference on Geographic Information Science, Palma (Mallorca, Spain) April 25th-27th 2002, 1–10.• G. Forbes. 2000. Urban roadway classification before the design begins, in Transportation Research E-Circular, Number E-C019.are not cited in the paper produced by H. Ziari, H. Behbahani and M. M. Khabiri. The Editorial Board of the Journal TRANSPORT and the Publishing House TECHNIKA have retracted the presented paper. The Editorial Board of the Journal TRANSPORT is AGAINST PLAGIARISM. Yours faithfully, on behalf of the Editorial Board of the Journal TRANSPORT, Editor-in-Chief, Prof. Adolfas Baublys.